Molecular, clinical and neuropsychological study in 31 patients with Kabuki syndrome and KMT2D mutations. Issue 3 (18th May 2017) - Lehman, N.; Mazery, A.C.; Visier, A.; Baumann, C.; Lachesnais, D.; Capri, Y.; Toutain, A.; Odent, S.; Mikaty, M.; Goizet, C.; Taupiac, E.; Jacquemont, M.L.; et al.
Abstract : Kabuki syndrome (KS—OMIM 147920) is a rare developmental disease characterized by the association of multiple congenital anomalies and intellectual disability. This study aimed to investigate intellectual performance in children with KS and link the performance to several clinical features and molecular data. We recruited 31 children with KMT2D mutations who were 6 to 16 years old. They all completed the Weschler Intelligence Scale for Children, fourth edition. We calculated all indexes: the Full Scale Intellectual Quotient (FSIQ), Verbal Comprehension Index (VCI), Perceptive Reasoning Index (PRI), Processing Speed Index (PSI), and Working Memory Index (WMI). In addition, molecular data and several clinical symptoms were studied. FSIQ and VCI scores were 10 points lower for patients with a truncating mutation than other types of mutations. In addition, scores for FSIQ, VCI and PRI were lower for children with visual impairment than normal vision. We also identified a discrepancy in indexes characterized by high WMI and VCI and low PRI and PSI. We emphasize the importance of early identification and intensive care of visual disorders in patients with KS and recommend individual assessment of intellectual profile. Abstract :